2019
DOI: 10.3906/vet-1905-48
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementary nano-ZnO on in vitro ruminal fermentation, methane release, antioxidants, and microbial biomass

Abstract: IntroductionMethane released during ruminal fermentation plays an important role in global warming [1,2]. One of the aims in ruminant nutrition is to reduce the release of methane from the rumen, without adverse effects on digestibility, animal health, and productivity [3]. Moreover, improvements of rumen microbial biomass and the antioxidant status of animals are attractive targets in feeding management. This requires the best supply of nutrients and supplementary minerals in diets. Zinc is a vital trace mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
4
2
Order By: Relevance
“…More specifically, the addition of ZnO from the start of the incubation (ZnO_0h) significantly (p<0.05) lowered the TGP in the first 48hrs of fermentations and tended (p=0.054) to be lower by the end of the 70hrs incubation compared to CON. These findings are not consistent with Riazi et al [43], who in an in vitro study with rumen juice collected from adult sheep, observed a significant increase of gas production when supplementing 20, 40 or 60 mg/kg DM of Zn (as ZnO) to a substrate already containing 25 mg/kg DM of Zn. However, the level of Zn supplementation used in this study was 500 mg/kg DM, which could explain the negative effect on TGP.…”
Section: Zinccontrasting
confidence: 87%
“…More specifically, the addition of ZnO from the start of the incubation (ZnO_0h) significantly (p<0.05) lowered the TGP in the first 48hrs of fermentations and tended (p=0.054) to be lower by the end of the 70hrs incubation compared to CON. These findings are not consistent with Riazi et al [43], who in an in vitro study with rumen juice collected from adult sheep, observed a significant increase of gas production when supplementing 20, 40 or 60 mg/kg DM of Zn (as ZnO) to a substrate already containing 25 mg/kg DM of Zn. However, the level of Zn supplementation used in this study was 500 mg/kg DM, which could explain the negative effect on TGP.…”
Section: Zinccontrasting
confidence: 87%
“…The inclusion of ZnNPs (100 and 200 mg/kg) has increased the volatile fatty acids, microbial crude protein, and degradation of organic matter at the 6th and 12th hours of incubation period under in vitro rumen fermentation conditions [49]. Similarly, improvement in the microbial biomass production and reduction in methane emanation were recorded with 20 mg of Zn as ZnNPs compared with other higher Zn levels (40 and 60 mg/kg dry matter, DM) during an in vitro fermentation study [50]. These positive effects are also seen in vivo with adult and/or growing animals; in ewes, the dietary supplementation of ZnNPs significantly increased the digestibility of DM, organic matter, nitrogen, and crude fiber-free extract compared with Zn larger particle and control ewes [51,52].…”
Section: Effects On Rumen Fermentation and Growth Performancementioning
confidence: 99%
“…Each nanomaterial has a specific function in the metabolism system. For example, ZnO nanoparticles as feed additives can improve the growth of rumen microorganisms and ruminal microbial protein synthesis (Huang et al, 2015) and raise the energy utilization efficiency (Riazi et al, 2019). Then, Se NPs can stimulate rumen microbial activity, digestive microorganisms or enzyme activity (Shi et al, 2011) and Se NPs exhibit lower toxicity than selenite (Çiçek et al, 2021).…”
Section: Freedom From Thirst Hunger and Malnutritionmentioning
confidence: 99%
“…From the examples that are mentioned above, we can conclude that nanoparticles can become an alternative solution to improve the dairy cattle welfare quality level in the aspect of freedom from thirst, hunger, and malnutrition. Because the data shows that Erciyes Üniv Vet Fak Derg 2022;19(1): 67-73 the usage of nanoparticles in the feed can improve digestibility, enzyme activity in the digestive system, and inhibit pathogen bacteria growth (Huang et al, 2015, Riazi et al, 2019. As a result, the evaluation of dairy cattle welfare improvement in this aspect can be done with body condition score (BCS) method (Spigarelli et al, 2020).…”
Section: Freedom From Thirst Hunger and Malnutritionmentioning
confidence: 99%